ASSOCIATION BETWEEN NUTRITIOUS STATUS AND LIFE QUALITY OF ELDER PEOPLE VISITING GERIATRIC CLINIC AT DR. SARDJITO HOSPITAL - Muhipah Muhipah; I Dewa Putu Pramantara; Deddy Nur Wachid Achadiono (Faculty of Medicine Universitas Gadjah Mada, 2016)
ABSTRACTBackground. Successful development in health sector cause shift in world population to older age. Yogyakarta Special Territory reveals highest percentage in amount of elderly people in Indonesia (13.7%). Prevalence of decrease in nutritional status rise along with age. Individual with low nutritional status is vulnerable to some diseases such as depression, cognitive disturbance and dementia progressivity. Nutritional status on elderly people is subject ignored in clinical practice. Prevention and early intervention is the best approach to obtain optimal nutrition.Objective. To identify association between nutritional statuses measured using MNA score and life quality measured with WHOQOL-BREF at elderly patient visiting geriatric clinic in Dr. Sardjito Hospital.Method. This research used cross-sectional design on elderly population in Dr. Sardjito Hospital. The research was conducted in October 2014. It includes elderly persons meeting inclusion and exclusion criteria, nutritional status assessed with MNA score and measurement of life quality with QHOQOL-BREF including four domains: physical aspect, psychological aspect, social relationship and environment.Result: There is significant correlation with p<0.001 between MNA and domain 1 (physical aspect) where Pearson correlation of 0.546 indicates positive correlation with weak correlation. Association of MNA and domain 2 (physical aspect) indicates significant correlation with p =0.006 with Pearson correlation of 0.435 indicating positive correlation with moderate correlation. There is significant correlation between MNA and domain 3 (social aspect) with p=0.005 and Pearson correlation of 0.437 indicating weak correlation. Association of MNA and domain four (environment aspect) indicate significant correlation with p=0.007 and Pearson correlations core of 0.426 indicating positive correlation with moderate correlation.Conclusion. The results indicate significant association between nutritional status (MNA) and life quality based on WHOQOL viewed from physical aspect (domain 1), psychological aspect (domain 2), social aspect (domain 30 and environmental aspect (domain 4) on elderly person.Keywords: Geriatrics, MNA, quality of life